Efficacy of surfactants in the sustainable restoration of the geotechnical properties of diesel-contaminated soil - Kumar A.; Mohan D.; Paramkusam B.R.; Singh A.P. (My University, 2025)
In this study, an evaluation of washing-based treatment for diesel-contaminated soil using non-ionic surfactants such as Tween-20, NP-9.5, and Triton X-100 at 5% (v/v) dosage for three days of washing in removing diesel as well as improvement of geotechnical properties was performed. The initial diesel content of 0.8 mg/g was identified using the gravimetric method in the soil. The geotechnical test results of the surfactant-washed diesel-contaminated soil show an increase in shear strength, a decrease in compression, and swelling. The contaminated and treated soil samples are also subjected to instrumental techniques like X-ray diffraction (XRD) and Fourier transform infrared radiation (FTIR). On analyzing the results from FTIR spectra, NP-9.5 is found to be the most efficient surfactant in removing the diesel. This study establishes that surfactant-aided soil washing is a prospective method for enhanced removal of diesel and leads to significant improvement in geotechnical properties of the treated soil. © 2023, The Author(s) under exclusive licence to Iranian Society of Environmentalists (IRSEN) and Science and Research Branch, Islamic Azad University.